Palbociclib combined with endocrine treatment in hormone receptor-positive, HER2-negative breast cancer patients with high relapse risk after neoadjuvant chemotherapy: subgroup analyses of premenopausal patients in PENELOPE-B - Marmé, Frederik; Martin, M.; Untch, M.; Thode, C.; Bonnefoi, H.; Kim, S. -B.; Bear, H.; Mc Carthy, N.; Gelmon, K.; García-Sáenz, J. A.; Kelly, C. M.; Reimer, T.; et al. (ESMO open, 2024)
Background - The PENELOPE-B study demonstrated that the addition of 1-year post-neoadjuvant palbociclib to endocrine therapy (ET) in patients with high-risk early breast cancer (BC) did not improve invasive disease-free survival (iDFS) compared to placebo. Here, we report results for premenopausal women. - Patients and methods - Patients with hormone receptor-positive, human epidermal growth factor receptor 2-negative BC at high risk of relapse [defined as no pathological complete response after neoadjuvant chemotherapy and a clinical, pathological stage, estrogen receptor, grading (CPS-EG) score ≥3 or 2/ypN+] were randomized to receive 13 cycles of palbociclib or placebo + standard ET. Ovarian function (OF) was evaluated by centrally assessed estradiol, follicle-stimulating hormone and anti-Müllerian hormone serum levels. - Results - Overall, 616 of 1250 randomized patients were premenopausal; of these, 30.0% were <40 years of age, 47.4% had four or more metastatic lymph nodes, and 58.2% had a CPS-EG score ≥3. 66.1% of patients were treated with tamoxifen alone, and 32.9% received ovarian function suppression (OFS) in addition to either tamoxifen or aromatase inhibitor (AI). After a median follow-up of 42.8 months (97.2% completeness) no difference in iDFS between palbociclib and placebo was observed [hazard ratio = 0.95, 95% confidence interval (CI) 0.69-1.30, P = 0.737]. The estimated 3-year iDFS rate was marginally higher in the palbociclib arm (80.6% versus 78.3%). Three year iDFS was higher in patients receiving AI than tamoxifen plus OFS or tamoxifen alone (86.0% versus 78.6% versus 78.0%). Patients receiving tamoxifen plus OFS showed a favorable iDFS with palbociclib (83.0% versus 74.1%, hazard ratio = 0.52, 95% CI 0.27-1.02, P = 0.057). Hematologic adverse events were more frequent with palbociclib (76.1% versus 1.9% grade 3-4, P < 0.001). Palbociclib seems not to negatively impact the OF throughout the treatment period. - Conclusions - In premenopausal women, who received tamoxifen plus OFS as ET, the addition of palbociclib to ET results in a favorable iDFS. The safety profile seems favorable and in contrast to chemotherapy palbociclib does not impact OF throughout the treatment period.
Online veröffentlicht: 4. Juni 2024, Artikelversion: 4. Juni 2024
Gesehen am 27.01.2025